Armenians in the Ottoman Empire Through the Records of the British Soldiers During World War I (According to the Kut Al-amara War Prisoners’ Memoirs) - Azizova, Elnura (Scholarya Demo Journal of Ruby, 2020)
Being one of the richest sources for cultural history, travel books, itineraries and memoirs are considered substantial sources for contemporary historians in the study of socio-cultural history of countries and societies which is as important as their political history. However, it is a fact that the identity of a travel book and diary writer is as important as the identity of authors of the first-hand sources referenced in political historiography. The issue of approaching the records of foreign travellers becomes a more sensitive topic when considering the records of foreign travellers about Armenian question, which turned into an important matter in the internal and foreign politics of the Ottoman Empire during its last quarter, despite it had hosted various religious and ethnic identities for a long period in its history. The political, cultural and religious situation of the Christians which constituted the majority of non-Muslim subjects in the Ottoman Empire, had great importance for their European co-religionists as the protectors of Christianity for centuries. Finally, when the Armenian rebellions occurred mostly as a result of provocations of foreign powers at the end of the 19th century, the interest of foreign diplomats and travellers increased towards the question. This paper will investigate data related political, social and cultural situation of the Armenians as Ottoman subjects within the context of diaries and memoirs of British war prisoners captured after Kut al-Amara war that took place near Baghdad on April 29, 1916, as one of the most severe defeats of the United Kingdom in its history. My Compain by Charles Townshend, Besieged in Kut and After by Barber, A Kut Prisoner by Bishop, In Kut and Captivity with the Sixth Indian Division by Sandes, The Secrets of a Kuttite by Mousley will be the main sources of the research.